Transglutaminase-mediated transamidation of serotonin, dopamine and noradrenaline to fibronectin: evidence for a general mechanism of monoaminylation - Hummerich, René; Thumfart, Jörg Oliver; Findeisen, Peter; Bartsch, Dusan; Schloss, Patrick (FEBS letters, 2012)
The activity of some small GTPases is regulated by covalent transamidation of serotonin (5-hydropxytryptamien) to glutamine residues of the enzymes. This process is mediated by transglutaminase (TGase) and is termed “serotonylation”. In addition, serotonylation of neural proteins and proteins of the extracellular matrix such as fibronectin has been demonstrated. Here we show that the catecholamines dopamine (DA) and noradrenaline (NA) inhibit serotonylation of fibronectin and that DA and NA themselves can be selectively transamidated into fibronectin by TGase. All three biogenic monoamines also block TGase-mediated transamidation of another monoamine, monodansylacadaverine, into fibronectin, suggesting a general mechanism of TGase-mediated “monoaminylation”.